Common Problems in Learning Simple Electrical Circuits at Elementary School and Their Solutions - Yusuf Barruly; Muhammad Rizal Habib; Handoko; Frida Destini (Journal of Advances in Physics Education, 2025)
Learning about simple electrical circuits is a crucial part of Science (IPA) education in elementary schools. However, its implementation often faces various obstacles. This study aims to identify the common problems in learning simple electrical circuits and to formulate effective solutions. Using a descriptive qualitative method with data collection through literature studies and interviews with sixth-grade teachers at SDN 1 Sidodadi, this research found three main issues: 1) Educators' lack of understanding and skills in teaching the concept of electrical circuits, 2) Students' low learning motivation and enthusiasm, often caused by the overuse of lecture methods, and 3) Lack or unavailability of tools and materials for practical activities. The solutions proposed to address these problems include: teachers participating in training to improve their professional competence, applying innovative learning models such as Project-Based Learning (PJBL) and experimental methods to increase student activity and motivation, and utilising appropriate learning media, ranging from realia (physical teaching aids) to PhET simulation media as a substitute when physical tools are unavailable. The conclusion of this study emphasises the importance of the teacher's role in continuously striving to improve the quality of learning through these various solutions, thereby achieving learning objectives effectively.